The Mechanics of a Strong Euro Area : IMF Policy Analysis - Koeva Brooks, Petya (International Monetary Fund, 2015)
Among member states, many structural weaknesses were exposed when economic performance declined significantly and financial markets became more discerning. This book focuses on the analytical underpinnings of real-time policy advice given to euro area policymakers during four cycles of the IMF's annual Article IV consultations (2012-15) with euro area authorities.